PAGAT gel dosimetry for everyone: gel production, measurement and evaluation. (20th July 2021) - Elter, A; Dorsch, S; Thomas, S; Hentschke, C M; Floca, R O; Runz, A; Karger, C P; Mann, P
Abstract: Polymer gel (PG) dosimetry is a valuable tool to measure complex dose distributions in 3D with a high spatial resolution. However, due to complex protocols that need to be followed for in-house produced PGs and the high costs of commercially available gels, PG gels are only rarely applied in quality assurance procedures worldwide. In this work, we provide an introduction to perform highly standardized dosimetric PG experiments using PAGAT (PolyAcrylamide Gelatine gel fabricated at ATmospheric conditions) dosimetry gel. PAGAT gel can be produced at atmospheric conditions, at low costs and is evaluated using magnetic resonance imaging (MRI). The conduction of PG experiments is described in great detail including the gel production, treatment planning, irradiation, MRI evaluation and post-processing procedure. Furthermore, a plugin in an open source image processing tool for post-processing is provided free of charge that allows a standardized and reproducible analysis of PG experiments.